Visual working memory in aphantasia: Retained accuracy and capacity with a different strategy. (October 2021) - Keogh, Rebecca; Wicken, Marcus; Pearson, Joel
Abstract: Visual working memory paradigms involve retaining and manipulating visual information in mind over a period of seconds. Evidence suggests that visual imagery (sensory recruitment) is a strategy used by many to retain visual information during such tasks, leading some researchers to propose that visual imagery and visual working memory may be one and the same. If visual imagery is essential to visual working memory task performance there should be large ramifications for a special population of individuals who do not experience visual imagery, aphantasia. Here we assessed visual working memory task performance in this population using a number of different lab and clinical working memory tasks. We found no differences in capacity limits for visual, general number or spatial working memory for aphantasic individuals compared to controls. Further, aphantasic individuals showed no significant differences in performance on visual components of clinical working memory tests as compared to verbal components. However, there were significant differences in the reported strategies used by aphantasic individuals across all memory tasks. Additionally, aphantasic individual's visual memory accuracy did not demonstrate a significant oblique orientation effect, which is proposed to occur due to sensory recruitment, further supporting their non-visual imagery strategy reports. Taken together these data demonstrate that aphantasic individuals are not impaired on visual working memory tasks, suggesting visual imagery and working memory are not one and the same, with imagery (and sensory recruitment) being just one of the tools that can be used to solve visual working memory tasks.